Analysis of The Role of Teachers in Developing Their Talents in Blind Children - Heny Irliany; Seviana Andriani Mening; Sarmila; Fahira Amanda Putri; Wilda Isna Kartika; Adharina Dian Pertiwi (Universitas Al-Hikmah Indonesia, 2026)
The limited understanding of teachers regarding the specific needs of visually impaired children often hinders the optimal development of their potential and talents. In fact, teachers play a central role in creating an inclusive learning environment. This study aims to explore the role of teachers in developing the talents of visually impaired students at SLB Pembina, East Kalimantan. This research employed a qualitative approach using participatory observation, in-depth interviews, and document analysis methods to obtain accurate data. The instruments used included observation sheets, interview guides, and document analysis sheets. The results show that teachers play a crucial role in helping visually impaired students develop their talents through an understanding of special needs, adapted learning methods, and emotional support. This study also found that an inclusive learning environment is essential for developing the talents of visually impaired students. Teachers must be able to adapt learning methods to the needs of visually impaired children. Therefore, this study recommends improving the quality of education for visually impaired children through inclusive learning environments and teacher training.